Comparative STEAM Competency Profiles of Secondary School Teachers in Riau, Indonesia - Abu Anwar; Decky Saputra; Rian Vebrianto (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
This study addresses the need to strengthen teachers' competencies in implementing the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach to support 21st-century skills in secondary education. The main problem is that STEAM implementation remains uneven across school types and teacher competency dimensions, especially in interdisciplinary planning, digital literacy, and project-based assessment. This study aims to analyze the comparative STEAM competency profile of secondary school teachers in Riau Province and to identify priority areas for professional development. A cross-sectional explanatory survey involved 42 teachers from SMA, MA, and SMK selected through proportional sampling. Data were collected using a 35-item Likert-scale questionnaire covering seven competency dimensions. The instrument was validated through expert judgment and construct testing, with a Cronbach's Alpha coefficient of 0.87. Data were analyzed using descriptive statistics and one-way ANOVA. The findings show that overall STEAM implementation is in the high category, with mean scores ranging from 3.31 to 3.54. Collaboration (3.54) and project-based assessment with 4C (3.52) scored highest, while digital literacy and technology (3.31) scored lowest. Comparative analysis indicates significant differences among school types, with SMA and MA generally scoring higher than SMK (p < 0.05). Theoretically, this study constructs a regional STEAM teacher competency profile that links 21st-century skills, ethno-STEAM, and project-based pedagogy. Practically, it identifies training priorities in digital pedagogy, interdisciplinary planning, and authentic assessment. In policy terms, it supports differentiated STEAM capacity building for SMA, MA, and SMK teachers.